PENGARUH PROFITABILITAS, KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020) - Resti Abdi Nursery; Nursiam Nursiam (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of profitability, investment decisions, funding decisions and dividend policy on firm value. The sample selection method uses a purposive sampling technique on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2020. The data used is secondary data obtained from the Indonesia Stock Exchange website (www.idx.co.id) and the websites of each company. The sample in this study amounted to 48 companies with a total sample data of 144. The data analysis technique used was multiple linear regression analysis with the help of SPSS Version 21. The results showed that the variables of profitability and investment decisions had an effect on firm value, while funding decisions and dividend policy has not affect on firm value.